2009
DOI: 10.1016/s1808-8694(15)30789-8
|View full text |Cite
|
Sign up to set email alerts
|

Functional alterations of the stomatognathic system in pacients with allergic rhinitis: case-control study

Abstract: Patients with allergic rhinitis have functional alterations in their stomatognathic system and an increase in nasal obstruction scores can be considered as a indication of such alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 8 publications
1
10
0
3
Order By: Relevance
“…Breathing difficulties and incoordination of breathing may be associated with decreased chewing duration, since asthma patients have difficulty in maintaining the balance required for breathing during feeding 18 . Using the tongue to help chewing, promoting food crushing, is consistent with the result of Lemos et al, who show that chewing is a learned function and may undergo changes 6 . The patients in the present study made a lot of random chewing sounds.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Breathing difficulties and incoordination of breathing may be associated with decreased chewing duration, since asthma patients have difficulty in maintaining the balance required for breathing during feeding 18 . Using the tongue to help chewing, promoting food crushing, is consistent with the result of Lemos et al, who show that chewing is a learned function and may undergo changes 6 . The patients in the present study made a lot of random chewing sounds.…”
Section: Discussionsupporting
confidence: 91%
“…Lemos et al, in 2009, pointed out that there is a relationship between oral breathing and the presence of changes in the swallowing pattern 6 . Drozdz et al reported that the act of swallowing depends on a complex and dynamic process using structures in common with the act of breathing, and, therefore, respiratory problems can cause swallowing difficulties 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Until the age of several months, the child is an obligate nasal breather, considering that, in infants, laryngeal descent has not yet occurred and the soft palate necessarily rests on the epiglottic vallecula, precluding the natural patency of the oral airways (17) . With growth, the nasal cavities may undergo anatomical changes, such as deviated septum and hypertrophies of the nasal turbinates (18)(19)(20)(21)(22)(23)(24)(25) . The nasal breathing mode can become predominantly oral and, thereby, bring functional changes not only to the respiratory process, but also to the stomatognathic system (19,20) .…”
Section: Discussionmentioning
confidence: 99%
“…Etiologies such as allergic rhinitis and nasal turbinate hypertrophy are generally the main causes of nasal obstruction and oral breathing. As a consequence of this altered respiratory pattern, children may present difficulties in speaking, chewing and swallowing, in addition to dental and postural alterations, which directly influence their development (20)(21)(22) . Therefore, it is important to perform prior, accurate diagnoses for adequate speech-language pathology prevention and treatment in children with mouth breathing.…”
Section: Discussionmentioning
confidence: 99%
“…Efeito da fisioterapia sobre os parâmetros ventilatórios e a dinâmica tóraco-abdominal de crianças respiradoras bucais Como consequência, alterações do complexo craniofacial podem estar presentes, influenciando negativamente as funções estomatognáticas e causando desequilíbrios posturais e respiratórios por uso excessivo da musculatura acessória da respiração [2][3][4] . Além dos prejuízos respiratórios e posturais, a respiração oral pode influenciar adversamente a qualidade de vida, principalmente por afetar o sono, o que prejudica o aprendizado e a cognição 5,6 .…”
unclassified